Arsenite removal from contaminated water by precipitation of aluminum, ferrous and ferric (hydr)oxides - Vasques, Isabela C. F.; Mello, Jaime W. V. de; Veloso, Renato W.; Ferreira, Vanessa de P.; Abrahão, Walter A. P. (Environmental Science and Pollution Research, 2018)
Several methods to remove arsenic from water have been considered, including co-precipitation with Fe and Al (hydr)oxides. Such compounds are considered very effective to remove As from contaminated water due to strong bindings between them. Three Fe:Al molar ratios (100:0, 80:20, and 60:40) were used to synthesize aluminum, ferrous, and ferric (hydr)oxides by precipitation in water highly contaminated with arsenite (50 and 500 mg L−1). The method was very efficient for all treatments (> 93%) at the beginning of the incubation period, excepted the one with 60:40 Fe(II):Al molar ratio at the higher As concentration (500 mg L−1) in which gibbsite was identified in precipitated phases. In spite of the high efficiency, however, the threshold for drinking water was not attained, mainly to the higher As concentration, even 84 days after precipitation. At this high concentration of arsenite, even the required threshold for effluent discharge was not attained in some treatments. The sludge resulting from treatments with higher As concentration were considered hazardous according to results from leaching test and corroborated by BCR extractions. Arsenic associated with Al and adsorbed phases were also assessed by extractions with NH4F and KH2PO4, respectively. In general, the presence of Al increased the efficiency as well as the stability of the sludge resulting from Fe (II) treatments, but did not affect Fe (III) treatments, which were more efficient for As removal.
Keywords: Wastewater treatment; Hematite; Al-goethite; Al-ferrihydrite; Gibbsite; Leaching test; BCR extraction